Tekanan Akademik pada Mahasiswa Semester 4 dalam Menyelesaikan Tugas Akhir Semester - Azhariah Fatya; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study is motivated by the increasing academic pressure experienced by fourth-semester university students in completing end-of-semester assignments. Academic demands, numerous deadlines, limited time management, and high expectations often trigger stress, anxiety, and decreased learning motivation among students. This condition may affect students’ emotional well-being and academic performance if not properly addressed. Therefore, this study aims to analyze the forms of academic pressure experienced by fourth-semester students and the factors influencing their difficulties in completing final semester assignments. The method used in this study is field research with a qualitative descriptive approach. Data were collected through observation and in-depth interviews with several fourth-semester students selected purposively. The data analysis technique employed the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The findings indicate that students experience various forms of academic pressure such as anxiety, fatigue, overthinking, lack of confidence, sleep disturbances, and difficulty managing study time. Several factors causing academic pressure include the accumulation of assignments, demands for good academic achievement, poor time management, limited social support, and personal problems experienced by students. In dealing with these pressures, students attempt to overcome them by arranging study schedules, seeking support from friends and family, taking short breaks, and improving self-motivation.